Lion Air's Strategy in Increasing Domestic Aviation Market Share at Makassar's Sultan Hasanuddin International Airport - Lala Ratu Iksanti; Danang Maulana (CV. Rayyan Dwi Bharata, 2023)
The world of aviation is currently experiencing quite rapid development with many requests for passengers to travel for leisure and business purposes. With this demand, Lion Air will increase its aviation market share strategy. This researcher aims. 1) To find out how to implement Lion Air's marketing strategy in increasing the aviation market share at Sultan Hasanuddin Makassar International Airport. 2) To find out what obstacles Lion Air is facing in increasing its market share at Sultan Hasanuddin International Airport. 3) To find out how the solution will be carried out by Lion Air in increasing the market share of domestic flights at Sultan Hasanuddin Makassar International Airport. This researcher uses a mixed method (mix method) with descriptive techniques. The instruments used to collect research data were the researchers themselves, observations, interviews, documentation to answer the research questions. Researchers conducted data analysis using qualitative and quantitative data analysis techniques. The results of this study indicate that the method of implementing Lion Air's marketing strategy in increasing the share of the aviation market provides information that there is Lion Air as a private airline that provides low-cost flight services while still prioritizing the best service and prioritizing safety. The obstacles faced in implementing this MPR strategy are HR who must be able to understand developments in IT technology, as well as HR who must be able to process research data that has been carried out in the field to observe the market. The solution that will be carried out is to choose human resources who are very competent in that field. Providing training, especially in the field of IT which is a means of communicating and providing information to the public.